Bis{2‐[(3, 5‐diphenyl‐1H‐pyrrol‐2‐ylidene‐κN)amino]‐3, 5‐diphenylpyrrol‐1‐ido‐κN}palladium(II): a homoleptic four‐coordinate tetraphenylazadipyrromethene complex of palladium. Issue 2 (10th January 2014) - Jones, Roderick C.; Müller‐Bunz, Helge; Evans, Paul; O'Shea, Donal F.
<x xml:space="preserve">Abstract</x> The structural chemistry of the title compound, [Pd(C32H22N3)2], at 173 K is described. The compound is comprised of two deprotonated (3, 5‐diphenyl‐1H‐pyrrol‐2‐yl)(3, 5‐diphenylpyrrol‐2‐ylidene)amine ligands coordinated to a central PdII cation, which lies on an inversion centre and has distorted square‐planar geometry. The Pd—N bond lengths range from 2.008 (4) to 2.014 (4) Å and the bite angle is 84.16 (14)°. The chelate plane makes a dihedral angle of 45.3 (2)° with respect to the central PdN4 plane, giving a stepped conformation to the molecule. The complex displays simple intramolecular C—H...N hydrogen bonds, while the unit cell consists of discrete monomeric Pd(C32H22N3)2 units which display intermolecular C—H...π interactions and limited intra‐ and intermolecular π–π stacking.